The impact of referendums on the centralisation of public goods provision: a political economy approach - Schnellenbach, Jan; Feld, Lars P.; Schaltegger, Christoph A. (Discussion paper series, 2007)
The paper compares decision-making on the centralisation of public goods provision in the presence of regional externalities under representative and direct democratic institutions. A model with two regions, two public goods and regional spillovers is developed in which uncertainty over the true preferences of candidates makes strategic delegation impossible. Instead, it is shown that the existence of rent extraction by delegates alone suffices to make cooperative centralisation more likely through representative democracy. In the non-cooperative case, the more extensive possibilities for institutional design under representative democracy increase the likelihood of centralisation. Direct democracy may thus be interpreted as a federalism-preserving institution.
Keywords: Arbeitspapier; Graue Literatur